A COMPUTATIONAL MODEL FOR GASIFICATION OF BIOMASS WASTE IN VIETNAM - Van, Hien Le (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Biomass is seen as an important part of a future, renewable energy mix, because unlike wind or solar energy, biomass based power generation can be operated on demand and can provide both heat and power. In this paper, a thermochemical model is used to predict the performance of a gasifier. Different biomass materials agricultural byproduct are tested using the model and forest residual is shown to be the most energetic one. For this material, the gasification temperature, syngas composition and calorific value are calculated. The effects of moisture content, air/fuel ratio, air inlet temperature are also investigated. The air inlet temperature is found to be the only way to increase the gas calorific value and cold gas efficiency. The air/fuel ratio, on the other hand, plays a rule key in controlling the gasification temperature and CO, H2 and CH4 ratio.